(untitled) (Global Journal of Science Frontier Research, 2020)
One of the essential problems of the use of energy of wind is the fact that to wind generator the wind can blow from the different sides and its wind wheel must be turned in the direction opposite to wind direction. There is a whole series of constructions of wind generator, the operating principle of which is based on what the different parts of the wind wheel has different aerodynamic drag with respect to the wind direction. However, in practice it does not succeed to obtain a large difference aeroditamicheskikh in the resistances indicated, which decreases the effectiveness of such generators. Furthermore, such wind generator are fairly complicated from a design point of view. But since such generators have wide practical application, of urgent appears the problem of developing of highly effective simple of wind generator. The creation of this device, which dependently on the wind direction directs, is one of the ways of creating this generator the air flow in one assigned direction. To the creation of this device is dedicated the article.